2018
DOI: 10.2147/ccid.s164748
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the therapeutic potential of a probiotic in a clinical population with chronic hand dermatitis

Abstract: BackgroundHand dermatitis or hand eczema (HD) is one of the most common dermatologic conditions. Lesions, scaling, pruritus and pain are chronic and relapsing. Improved HD has been reported with the probiotic composed of Lactobacillus acidophilus CL1285, Lactobacillus casei LBC80R and Lactobacillus rhamnosus CLR2 (Bio-K+).PurposeInvestigation of the therapeutic potential of this probiotic as the sole systemic treatment for adults with nonacute HD.Subjects and methodsA single-center study documented clinical ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Nevertheless, one trial reported that probiotics alone provided little benefit, yet reported significant clinical improvement when combined with the potential prebiotic lactoferrin [ 85 , 86 ]. Other recent studies have shown potentially beneficial effects of oral probiotics in plaque psoriasis [ 87 , 88 ], adult AD [ 89 ], hand dermatitis [ 90 ], papulopustular rosacea, seborrhoeic dermatitis [ 86 ] and dandruff [ 91 ].…”
Section: Human Clinical Trials Investigating Microbial Treatments For Skin Conditionsmentioning
confidence: 99%
“…Nevertheless, one trial reported that probiotics alone provided little benefit, yet reported significant clinical improvement when combined with the potential prebiotic lactoferrin [ 85 , 86 ]. Other recent studies have shown potentially beneficial effects of oral probiotics in plaque psoriasis [ 87 , 88 ], adult AD [ 89 ], hand dermatitis [ 90 ], papulopustular rosacea, seborrhoeic dermatitis [ 86 ] and dandruff [ 91 ].…”
Section: Human Clinical Trials Investigating Microbial Treatments For Skin Conditionsmentioning
confidence: 99%
“…Associations between the human microbiome and a range of painful conditions have been reported. These conditions include endometriosis (Leonardi et al, 2019), fibromyalgia (Malatji et al, 2017), myalgic encephalomyelitis/chronic fatigue syndrome (Nagy-Szakal et al, 2017), interstitial cystitis/bladder pain syndrome (Nickel et al, 2019), chronic prostatitis/chronic pelvic pain syndrome (Shoskes et al, 2016), dermatitis (Gulliver et al, 2018), and inflammatory bowel disease (Knights et al, 2013). Furthermore, there is emerging experimental evidence that changing the gut microbiome through probiotics (Lactobacillus casei Shirota (Lei et al, 2017), L. gasseri OLL2809 (Itoh et al, 2011), and combined L. acidophilus, L. plantarum, L. fermentum and L. gasseri (Khodaverdi et al, 2019)) reduces pain in people with knee osteoarthritis (Lei et al, 2017), and endometriosis (Itoh et al, 2011;Khodaverdi et al, 2019).…”
Section: Environmental Microbiomesmentioning
confidence: 99%
“…In an exploratory, single‐center, open‐label trial of 30 adult patients with mild to severe CHE >6 months, supplementation with daily Lactobacillus acidophilus , Lactobacillus asei , and Lactobacillus rhamnosus for 12 weeks resulted in an improvement of 1–50% (86%) or 75–100% improvement (27%) based on PGA scoring. Furthermore, patients reported relief of pruritus (59%), development of new lesions (52%), and overall skin condition improvement (45%) within 2 weeks (Gulliver et al, ). However, the small sample size, lack of placebo control, withdrawal due to diarrhea likely resulting from the study medication N = 1, aggravation of eczema N = 1, and withdrawal due to consent N = 5 and loss‐to‐follow up N = 1 should be noted.…”
Section: Systemic Agentsmentioning
confidence: 99%